On the bulk biomechanical behavior of densely cross-linked dentin matrix: The role of induced-glycation, regional dentin sites and chemical inhibitor. (March 2020) - Alania, Yvette; Trevelin, Livia T.; Hussain, Mohammad; Zamperini, Camila A.; Mustafa, Gresa; Bedran-Russo, Ana K.
Abstract: Collagen glycation takes place under physiological conditions during chronological aging, leading to the formation of advanced glycation end-products (AGEs). AGEs accumulation induces non-enzymatic collagen cross-links increasing tissue stiffness and impairing function. Here, we focused on determining the cumulative effect of induced glycation on the mechanical behavior of highly collagen cross-linked dentin matrices and assess the topical inhibition potential of aminoguanidine. Bulk mechanical characterization suggests that early glycation cross-links significantly increase the tensile strength and stiffness of the dentin matrix and promote a brittle failure response. Histologically, glycation yielded a more mature type I collagen in a densely packed collagen matrix. The time-dependent effect of glycation indicates cumulative damage of dentin matrices that is partially inhibited by aminoguanidine. The regional dentin sites were differently affected by induced-glycation, revealing the crown dentin to be mechanically more affected by the glycation protocol. These findings in human dentin set the foundation for the proposed in vitro ribose-induced glycation model, which produces an early matrix stiffening mechanism by reducing tissue viscoelasticity and can be partially inhibited by topical aminoguanidine. Graphical abstract: Image 1 Highlights: Glycation of highly cross-linked dentin extracellular matrix results in an immediate brittle-like biomechanical behavior. Distinct regional effects indicates higher susceptibility to glycation by crown extracellular matrix. Damage to the biomechanics of dentin matrices is cumulative and partially inhibited by topical exposure to aminoguanidine.